FT-ICR-MS characterization of organic matter and further sample details of Bangladeshi aquifer sediment incubated with aquifer recharge waters - Pracht, Lara E; Tfaily, Malak M; Ardissono, Robert J; Neumann, Rebecca B (Supplement to: Pracht, LE et al. (2018): Molecular characterization of organic matter mobilized from Bangladeshi aquifer sediment: tracking carbon compositional change during microbial utilization. Biogeosciences, 15(6), 1733-1747, https://doi.org/10.5194/bg-15-1733-2018, 2017)
Bioavailable organic carbon in aquifer-recharge waters and sediments can fuel microbial reactions with implications for groundwater quality. A previous incubation experiment showed that sedimentary organic carbon (SOC) mobilized off sandy sediment collected from an arsenic-contaminated and methanogenic aquifer in Bangladesh was bioavailable; it was fermented into methane. We used high-resolution mass spectrometry to molecularly characterize this mobilized SOC, reference its composition against dissolved organic carbon (DOC) in aquifer recharge water, track compositional changes during incubation, and advance understanding of how composition relates to bioavailability in anaerobic conditions.